Vesicle Docking to the Spindle Pole Body Is Necessary to Recruit the Exocyst During Membrane Formation in Saccharomyces cerevisiae - Mathieson, Erin M. (The American Society for Cell Biology, 2010)
During meiosis II in Saccharomyces cerevisiae, the cytoplasmic face of the spindle pole body, referred to as the meiosis II outer plaque (MOP), is modified in both composition and structure to become the initiation site for de novo formation of a membrane called the prospore membrane. The MOP serves as a docking complex for precursor vesicles that are targeted to its surface. Using fluorescence resonance energy transfer analysis, the orientation of coiled-coil proteins within the MOP has been determined. The N-termini of two proteins, Mpc54p and Spo21p, were oriented toward the outer surface of the structure. Mutations in the N-terminus of Mpc54p resulted in a unique phenotype: precursor vesicles loosely tethered to the MOP but did not contact its surface. Thus, these mpc54 mutants separate the steps of vesicle association and docking. Using these mpc54 mutants, we determined that recruitment of the Rab GTPase Sec4p, as well as the exocyst components Sec3p and Sec8p, to the precursor vesicles requires vesicle docking to the MOP. This suggests that the MOP promotes membrane formation both by localization of precursor vesicles to a particular site and by recruitment of a second tethering complex, the exocyst, that stimulates downstream events of fusion.